Idarucizumab: What Should We Know? - Cortese, Francesca; Calculli, Giacinto; Gesualdo, Michele; Cecere, Annagrazia; Zito, Annapaola; De Vito, Fiorella; Carbonara, Rossella; Carbonara, Santa; Cortese, Anna M.; Ciccone, Marco Matteo (Current Drug Targets, 2018)
Background: Idarucizumab, a humanized monoclonal antibody fragment acting as a specific antidote for dabigatran, is approved for reversing the dabigatran-associated possible bleeding from critical sites or bleeding persisting despite local post-procedure haemostasis. Moreover, it can also be applied to reverse the dabigatran anticoagulant activity in emergency surgery or in other invasive procedure at high risk of bleeding. Objective: In this study, we discuss idarucizumab in light of the available literature data by conducting extensive research in the PubMed, EMBASE and Cochrane Library on the topic, using idarucizumab, dabigatran and their combinations as Mesh terms, and focusing on high impact investigations. Results: Several studies have demonstrated the capacity of idarucizumab to reverse laboratory measures of dabigatran-associated coagulopathy, however its efficacy and safety in real world patients are still not very clear because of the scarcity of available data which should be assessed with an extensive post market surveillance. Conclusion: The introduction of idarucizumab as dabigatran antidote in clinical practice represents a useful tool for clinicians. The possibility to rapidly restore the anticoagulation activity of dabigatran makes its use simpler and more manageable.
Keywords: Idarucizumab